ROLE OF INHERENT IMMUNITY AND MICROORGANISMS OF BIOTOPES OF MUCOUS MEMBRANE OF WOMEN’S GENITOURINARY TRACT IN PATHOGENESIS OF CHLAMYDIA INFECTION - M. S. Afanasiev; A. V. Karaulov; V. A. Aleshkin; S. S. Afanasiev; Yu. V. Nesvizhsky; E. A. Voropaeva (Сеченовский вестник, 2010)
Aim. Study of Toll-like receptors (TLR) role and microorganisms of bioptopes of genitourinary tract in pathogenesis of genitourinary chlamydiasis.Methods. 41 female patients with acute genitourinary chlamydiasis; 29 - with chronic genitourinary chlamydiasis; 30 with genitourinary chlamydiasis in ananamnesis were included into the study; 32 healthy women served as controls. Beyond standard clinical and laboratory investigation, expression of TLR in genitourinary mucous membrane was studied.Results. Elevation of expression of TLR-2 and TLR-4 genes in cervical canal and urethra, associated with both Chlamydia and other microorganisms (exciters of sexually transmitted infections and opportunistic), correlating with clinical severity, was detected in acute genitourinary chlamydiasis. In chronic and/or asymptomatic genitourinary chlamydiasis TLR-2 and TLR-4 genes expression was lower, than in normal conditions.Conclusion. TLR-2 and TLR-4 genes expression can be considered as stratification criteria for determination of severity of inflammatory process in genitourinary tract, induced by Chlamydia. Low levels of TLR-2 and TLR-4 expression can indicate the start of chronic phase of Chlamydia infection.